PENGEMBANGAN BAHAN AJAR MATERI ALJABAR BERORIENTASI KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK - Rahmat Syukur; Rizki Wahyu Yunian Putra; Abi Fadila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop an algebra teaching materials oriented toward students' mathematical representation ability for the junior high school (SMP/MTs) level. The research employs a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The validity of the teaching materials was assessed by material and media experts, and its effectiveness was tested on 36 eighth-grade MTs students. The material expert validation yielded an average score of 3.67, categorized as valid, while the media expert validation resulted in an average score of 4.00, also categorized as valid. Student response questionnaires on module attractiveness showed a score of 3.26 (very attractive) from a small group of 10 students and 3.28 (very attractive) from a larger group of 26 students. The module's effectiveness was measured using the N-Gain score, which reached 0.57 classified as moderate indicating the materials are fairly effective. It can be concluded that the algebra teaching materials developed in this study, oriented toward students’ mathematical representation ability, is highly suitable to be used as a learning resource for SMP/MTs students.